Borges de Medeiros e os Coronéis da Campanha : o controle do reduto federalista nos dois primeiros mandatos de Borges de Medeiros (1898-1908) - Groders, Jéssica Adriana Pacheco (2018)
The almost forty years of Riograndense Republican Party (PRR) rule in the Rio Grande do Sul state are marked by the strong influence of the leaders Julio Prates de Castilhos and Antonio Augusto Borges de Medeiros. To further understand the republicanism imposed by this party, which in Rio Grande do Sul was based on Castilhos' revisit of the positivist theory of Auguste Comte, it‟s necessary to clarify the bases used by the PRR to consolidate its presence on the state presidency. Also, there‟s no way to approach this subject without mentioning the Federalist Revolution (1893-1895), the main obstacle to obtaining control of the state. Even with the Federalist Party‟s defeat, this revolution represented clear opposition to Castilhos‟ rule mainly on the Campanha region (a widely known Federalist outpost). After this conflict ended and Castilhos died, he was recognized as the main Republicanism articulator and Medeiros its consolidator. This Master‟s dissertation, developed on the Political History‟s line of research of the Post-Graduation program of University of Passo Fundo, focuses on the party‟s consolidation under Medeiros‟ leadership. His way to strengthen republicanism surpasses the alliance made with local „coronéis‟, and exactly within this context this dissertation seeks to understand how the political relationship between the State President Borges de Medeiros and the „Coronéis de Campanha‟, leaders based on the state‟s frontier, a federalist space, worked. To uncover that matter, a research was conducted using as main information sources the letters sent from the border townships of Bagé, Jaguarão and Santana do Livramento to the state president Medeiros during his first two mandates (1898- 1908). Correspondence that, beyond political issues, expresses the reciprocal and dependent relationship established by the Campanha‟s citizens and the State Government in the end of the XIX and beginning of the XX century.